Pengaruh Stres Kerja Terhadap Kinerja Karyawan Penyemprot Pestisida di PT. X - Rizki Asih Gustara; Yeni Ayu Astuti; Mayang Dwi Octavia; Salianto, Salianto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Every employee must have faced work-related stress. Although there are times when work stress is beneficial, if it is excessive it will have a negative impact which is especially detrimental to employee performance. So it is necessary to control and prevent stress in the workplace. The purpose of this research is to examine how the performance of employees of PT. X is affected by stress at work. For this study, a sample of 13 workers who sprayed pesticides were interrogated. The data for this study came from a questionnaire. Quantitative descriptive analytic approach is used in this research. Simple linear regression analysis yields Y = 2.435 + 0.770X and partially t count for the work stress variable (X) of 11.133 and t count value 11.133 > t table value 2.201 and also a significant value less than 0.05 (0.000 <0 , 05). This proves that there is a strong relationship between stress at work and worker performance. So companies should offer advice for managing work stress and other outside activities that can energize the body and mind.